Inflammatory Th1 and Th17 in the Intestine Are Each Driven by Functionally Specialized Dendritic Cells with Distinct Requirements for MyD88 - Liang, Jie; Huang, Hsin-I; Benzatti, Fernanda P. [UNESP]; Karlsson, Amelia B.; Zhang, Junyi J.; Youssef, Nourhan; Ma, Averil; Hale, Laura P.; Hammer, Gianna E. (Cell Press, 2016)
Normal dynamics between microbiota and dendritic cells (DCs) support modest numbers of T cells, yet these do not cause inflammation. The DCs that induce inflammatory T cells and the signals that drive this process remain unclear. Here, we demonstrate that small intestine DCs lacking the signaling attenuator A20 induce inflammatory T cells and that the signals perceived and antigen-presenting cell (APC) functions are unique for different DC subsets. Thus, although CD103(+)CD11b(+) DCs exclusively instruct IFN gamma(+) T cells, CD103(+)CD11b(+) DCs exclusively instruct IL-17(+) T cells. Surprisingly, APC functions of both DC subsets are upregulated in a MyD88-independent fashion. In contrast, CD103(-)CD11b(+) DCs instruct both IFN gamma(+) and IL-17(+) T cells, and only the IL-17-inducing APC functions require MyD88. In disease pathogenesis, both CD103(-)CD11b(+) and CD103(+)CD11b(+) DCs expand pathologic Th17 cells. Thus, in disease pathogenesis, specific DCs instruct specific inflammatory T cells.